Analisis Yuridis Pemberian Abolisi terhadap Pidana Korupsi dalam Studi Kasus Tom Lembong - Muzakki Muzakki; Fina Rosalina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study is motivated by the granting of abolition to Tom Lembong in a corruption case, which has raised debate regarding its compatibility with the principle of legal certainty, considering that corruption is categorized as an extraordinary crime requiring consistent law enforcement. The objective of this study is to analyze the legal framework governing abolition as a presidential prerogative and to examine its implications for the principle of legal certainty within Indonesia's criminal justice system. This research employs a normative legal research method using statutory, conceptual, and case approaches. Legal materials were collected through library research consisting of primary, secondary, and tertiary legal sources and were analyzed qualitatively using a descriptive-analytical method. The findings indicate that the President's authority to grant abolition is constitutionally regulated under the 1945 Constitution of the Republic of Indonesia with due consideration from the House of Representatives. Nevertheless, granting abolition in corruption cases that have undergone judicial proceedings may create legal uncertainty by affecting the finality of court decisions, the principle of equality before the law, and the effectiveness of anti-corruption enforcement. Therefore, clearer regulations concerning the requirements, limitations, and procedures for granting abolition are necessary to ensure that the exercise of presidential prerogative remains consistent with the principles of the rule of law, legal certainty, and justice for society.